Association between physical education, school-based physical activity, and academic performance: a systematic review (Asociación entre la educación física, la actividad física en la escuela, y el rendimiento académico: una revisión sistemática) - Adilson Marques; Francisco Gómez; João Martins; Ricardo Catunda; Hugo Sarmento (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: The time allocation for physical education school-based physical activity is often replaced with other classes in an effort to increase children’s academic performance. However, a growing body of literature suggests that physical activity either had no effect on academic performance or that it enhanced it. Objective: The purpose of this report is to perform a systematic review of the evidence on the associations between physical education and school-based physical activity, and academic performance. Design: Systematic review. Methods: Studies were identified through research of the PubMed, Sportdiscus, and Web of Science databases from 2000 through 2016. The titles and abstracts were screened for eligibility, the methodological quality of the studies was rated, and data was extracted. The main exposure was physical education or school-based physical activity. For the main outcome, studies had to report at least one academic performance measure. Results: A total of 12 articles met the inclusion criteria; four of them were cross-sectional, two longitudinal, two quasi-experimental and four interventional studies. Seven articles found a positive association between physical education or school-based physical activity and academic performance, four found no association and in one there was a positive association for 3rd grade students and a negative association for 2nd grade students. Conclusion: In general, results of the review support that physical education or school-based physical activity is positively associated with academic performance in children.